Tracheotomy decannulation in the pediatric age group: an enigma - Munjal, Manish; Munjal, Shubham; Arora, Vineeta; Chauhan, Swati; Bansal, Garima; Sandhu, Lovleen; Gill, Karambir; Bhargava, Sidharth; Kakkar, Shruti; Goraya, Jatinder; Arora, Kamal; Nain, Fatehvir Singh; et al. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Asclepiades was the pioneer of a successful pediatric tracheostomy which is the commonest surgery undertaken in the critically-ill child for prolonged airway, ventilatory support and bronchial toilet. Newborn/neonatal intensive care units globally consider tracheostomy as a priority in their protocols, in the pediatric individual who have a high probability of retaining the endotracheal tube for a long period. The removal of the tracheostomy tube is called decannulation. Reinsertion of the tracheostomy tube within 48-96 hours is labelled failed decannulation. Sensorium, ability to cough, laryngo-tracheal secretions, and blood gas levels are crucial parameters prior to decannulation. Granulomas in the supra-glottic and subglottic region lead to stenosis which is one of the common reasons for an unsuccessful outcome. Mortality is usually secondary to the underlying ailment and, not the tracheotomy itself.